PENERAPAN BUKU PINTAR CEPAT BACA SISWA TERHADAP KEMAMPUAN MEMBACA SISWA KELAS 1 SD ISLAM TERPADU ASSALAFIYYAH PAMBON TAHUN PELAJARAN 2020/2021 - Nurhaningtyas Agustin (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
Learning of reading provides students with the knowledge and ability to master reading techniques, and capture the reading content well and be able to write it correctly. Reading activities become part of human life in everyday life, through reading activities we can find knowledge, and open insights.This study aims to describe students' reading ability with the application of fast-reading smart books that have previously been developed in previous research. The method in this study is a quantitative approach with a type of experimental research that uses pre test post test design. The subjects in this study were grade 1 students of SD Islam Terpadu Asslafiyyah Pambon Tuban with a total of 7 students. The results of the student's research were completed with KKM ≥70 with a percentage of student completion obtained by 100%. After the calculation of The Normality Gain Test explained that the improvement of learning outcomes obtained an increase in the high category with the number of 5 students, and moderate 2 students. Psychomotor observations gained an average of 94. So it can be said that the use of Smart Book Quick Read that has been in grade 1 of SD Islam Terpadu Assalafiyyah Pambon Tuban can improve the cognitive and psychomotor learning outcomes of students